COVID-19 and Scottish Independence: The Instrumentalisation of the Pandemic in the Constitutional Debate - Nelly Gérard (Revue Française de Civilisation Britannique)
The Covid-19 pandemic unfolded in the UK in a specific context where, in the aftermath of the Brexit referendum, much of the political scene had been dominated by constitutional politics. Feeding into this debate about Scotland’s status within the UK, the Covid-19 crisis and its management became yet another argument for political parties to legitimize their constitutional policies. Drawing on the Discourse-Historical Approach and using party manifestos, this article investigates how the Covid-19 pandemic is constructed in the discourses of the Scottish National Party (SNP) and the Scottish Conservative and Unionist Party, and how it fits into the debate on Scotland’s constitutional future. The article concludes that the Covid-19 pandemic is instrumentalised in the larger constitutional debate, either to promote independence and constitutional reform in the case of the SNP, or to undermine nationalist rhetoric through the use of depoliticisation strategies in the case of the Scottish Conservative Party.